Correlation between serum vitamin D, prolactin levels, and clinical depression at a tertiary care centre: A cross-sectional study. - Dr. Akanksha; Dr. Vivek Sinha (Student’s Journal of Health Research Africa, 2025)
Background Depression is a highly prevalent psychiatric disorder with complex etiopathogenesis involving neuroendocrine and biochemical factors. Emerging evidence suggests that serum vitamin D deficiency and hyperprolactinemia may play contributory roles in the development and severity of depressive symptoms. Objective: To evaluate the correlation between serum vitamin D and prolactin levels with the severity of clinical depression in patients attending a tertiary care center. Methods A cross-sectional observational study was conducted involving 120 adult patients diagnosed with clinical depression based on DSM-5 criteria. The severity of depression was assessed using the Hamilton Depression Rating Scale (HAM-D). Serum 25-hydroxy vitamin D [25(OH)D] and prolactin levels were measured using chemiluminescent immunoassay (CLIA). Vitamin D status was classified as deficient (<20 ng/mL), insufficient (20–30 ng/mL), and sufficient (>30 ng/mL). Pearson correlation, ANOVA, and independent t-tests were applied for statistical analysis. Results The mean age of participants was 36.4 ± 10.2 years, with 60.8% being female. Mean serum vitamin D and prolactin levels were 17.8 ± 6.9 ng/mL and 24.6 ± 9.1 ng/mL, respectively. Vitamin D deficiency was present in 70% of patients and associated with higher HAM-D scores (22.1 ± 5.4; p < 0.01). A moderate negative correlation was observed between vitamin D levels and HAM-D scores (r = -0.54, p < 0.01), while prolactin levels showed a weak positive correlation with HAM-D scores (r = 0.28, p = 0.03). Conclusion Vitamin D deficiency and elevated prolactin levels are significantly associated with increased severity of clinical depression. Routine assessment of these biomarkers may aid in the comprehensive evaluation and management of depressive disorders. Recommendations Routine screening of serum vitamin D and prolactin levels should be considered in depressive patients to guide individualized treatment strategies and improve overall management of clinical depression.